EMERGENCY NURSING CARE FOR PATIENTS WITH SEPTIC SHOCK - Sriwilai, Worralug (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
Septic shock remains a leading cause of mortality in emergency patients. Delayed assessment, screening, diagnosis, and treatment of sepsis can lead to septic shock, which has a high mortality rate. Therefore, nursing care using sepsis and septic shock guidelines with early goal-directed therapy (EGDT) in the first hour can reduce the mortality rate. Emergency nurses should have the knowledge, skills, and experience to assess, monitor, and care for patients with septic shock, ensuring they receive EGDT within the first hour to reduce organ failure and mortality rates. This article synthesizes guidelines and care management for emergency patients with septic shock. The information encompasses essential elements of care, including the definition, pathophysiology of septic shock, septic shock guidelines, and a case study of a patient with septic shock receiving treatment in the accident and emergency room. The outcome of the patient was positive, ensuring safety and subsequent admission to the general ward.